A comprehensive structured review of organizational commitment and job satisfaction - Dean Nelson Mojolou; Fearozh Madli; Suddin Lada; Ferawati Usman; Nurul Hidayathulzakiyah (Penerbit Akademi Baru, 2025)
This paper presents a comprehensive, structured review of the existing literature on organizational commitment and job satisfaction, two critical constructs in organizational behavior and human resource management. The study employs a systematic literature review (SLR) methodology to synthesize and analyze the body of knowledge on these topics. Data were extracted from three prominent databases— Scopus, EconBiz, and ERIC—using a rigorous search protocol that included criteria such as language (English), publication type (peer-reviewed journal articles), timeline (2000–2023), and subject area (business, management, psychology, and education). The review identifies key themes, theoretical frameworks, and empirical findings that elucidate the relationship between organizational commitment and job satisfaction, as well as their antecedents and outcomes. The findings reveal that organizational commitment and job satisfaction are interrelated constructs that significantly influence employee performance, retention, and organizational success. The study also highlights gaps in the literature, such as the need for more cross-cultural studies and longitudinal research to understand the dynamic nature of these constructions. By providing a structured overview of the field, this paper contributes to academic discourse and offers practical insights for managers and policymakers aiming to enhance employee engagement and organizational effectiveness.